MANAJEMEN BERBASIS SEKOLAH (Alternatif Peningkatan Mutu Pendidikan Madrasah) - HM, Muhammad Anwar (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This paper is intended to uncover the core issues that exist in madrasah as aroot barrier to the improvement of its quality. The results show that madrasah confronts a dilemma as an educational institution. As an educational institution, madrasah should be given broad discretion in its management, especially in the era of regional autonomy. In today’s era of autonomy, one of the concepts that canbe applied to improve the quality of education is the School-Based Management (SBM). The paper argues that although madrasah is under the auspice of the Department of Religion, the concept of School-Based Management (MBS) canbe adopted by madrasah on the basis of its suitability as strategies in coping with madrasah’s problems. The implementation of Madrasah-Based Management is intended to improve the quality of madrasah as an Islamic institution.